Inhibition of the cluster of differentiation 14 innate immunity pathway with IAXO-101 improves chronic microelectrode performance. (25th January 2018) - Hermann, John K; Ravikumar, Madhumitha; Shoffstall, Andrew J.; Ereifej, Evon S; Kovach, Kyle M; Chang, Jeremy; Soffer, Arielle; Wong, Chun; Srivastava, Vishnupriya; Smith, Patrick; Protasiewicz, Grace; Jiang, Jingle; et al.
Abstract: Objective . Neuroinflammatory mechanisms are hypothesized to contribute to intracortical microelectrode failures. The cluster of differentiation 14 (CD14) molecule is an innate immunity receptor involved in the recognition of pathogens and tissue damage to promote inflammation. The goal of the study was to investigate the effect of CD14 inhibition on intracortical microelectrode recording performance and tissue integration. Approach . Mice implanted with intracortical microelectrodes in the motor cortex underwent electrophysiological characterization for 16 weeks, followed by endpoint histology. Three conditions were examined: (1) wildtype control mice, (2) knockout mice lacking CD14, and (3) wildtype control mice administered a small molecule inhibitor to CD14 called IAXO-101. Main results . The CD14 knockout mice exhibited acute but not chronic improvements in intracortical microelectrode performance without significant differences in endpoint histology. Mice receiving IAXO-101 exhibited significant improvements in recording performance over the entire 16 week duration without significant differences in endpoint histology. Significance . Full removal of CD14 is beneficial at acute time ranges, but limited CD14 signaling is beneficial at chronic time ranges. Innate immunity receptor inhibition strategies have the potential to improve long-term intracortical microelectrode performance.